Nucleus patterns of zoea I larvae (Crustacea: Decapoda) in the context of taxonomy - Meyer, Roland; Martin, Jana; Melzer, Roland R. (Zootaxa, 2010)
Using DAPI as a nucleus marker, we studied zoeas of 6 decapods (Palaemon adspersus Rathke, 1837; Palaemon elegans Rathke, 1837; Porcellana platycheles (Pennant, 1777); Pisidia longicornis (Linnaeus, 1767); Xantho hydrophilus (Herbst, 1780) Xantho pilipes A. Milne Edwards, 1867) representing one species pair of Palaemonidae (Caridea), Porcellanidae (Anomura) and Xanthidae (Brachyura) each, with special reference to the telson, and correlated our observations with the general morphological features of the zoeas. The different taxa exhibit specific features with respect to the distribution of nuclei, the patterns they exhibit, their size, density and numbers, thus being sets of characters potentially useful for taxonomic descriptions and diagnoses especially on the “above-species”-level. We discuss how nuclear patterns and classical morphological and/or morphogenetical features normally examined in zoeal larvae are related, and give some ideas on how “nucleus”characters can contribute to taxonomic descriptions.